COSMETICS PRODUCTION UNDER OEM&ODM LICENSE - Gabdulina, Botagoz; Medeubekova, Lazzat; Umurzakova, Madina; Kuttybayeva, Ubaida (Nazarbayev University, Graduate School of Business, 2019)
Ana Global (hereinafter – the Company, Ana Global) is a company that has created a brand concept consisting of skincare products in South Korea. Now the founder of the Company intends to open the production factory in Kazakhstan focused on B2B business. Goal: The Company is going to run a high quality licensed cosmetic and beauty care product manufacturing company whose services will be provided for the best Korean cosmetic companies, and end products will be sold in Kazakhstan. The target clients are not limited by Korean companies only. After successful implementation of the project and following a positive reputation on the new market, the Company expects further interest from the side of European, Russian, and other brands whose products are in demand on the Kazakh market. The Company intends to build a business that will be listed amongst the top 20 cosmetic and beauty care brands in the CIS. The following business plan explains the Company’s potential market, value proposition, and competitiveness of the project. The financial part provides a detailed view of its sales and profit forecasts as well as financial indicators of the project. Our evaluation of business will include strategy analysis and financial plans.
Keywords: Type of access: Restricted; Skin care; B2B